Interaction Behaviors of Bilingual Parents With Their Young Children With Autism Spectrum Disorder. (21st December 2018) - Hudry, Kristelle; Rumney, Lisa; Pitt, Nicole; Barbaro, Josephine; Vivanti, Giacomo
Abstract : Given concerns that bilingual exposure might confuse children with disabilities—including autism spectrum disorder (ASD)—bilingual parents may restrict exposure to one language, often the community-dominant language. We investigated a potential consequence of this decision; the possibility that non-native language use might influence parental communicative behaviors during interaction with the child. We recruited 39 parent–child dyads, each with a young child with ASD (mostly boys) and parent/carer (mostly mothers). Parents were either monolingual speakers of community-dominant English ( n  = 20) or bilingual with English as the second language ( n  = 19). We confirmed our assumption that the latter group would have significantly poorer non-native English language via standardized assessment of expressive vocabulary, and ensured children were matched on age, ASD symptoms, and developmental level. We sampled parent–child interaction—including in each of bilinguals' native and non-native languages—and coded parents' amount and complexity of speech, communicative synchrony, and imitations and expansions of their child's speech. Few differences presented across bilingual parents' native versus non-native language samples, but this group showed reduced synchrony and use of expansions compared to monolinguals. Further, bilinguals' English-language knowledge was associated with self-reported comfort using this language and with two coded interaction measures. These empirical data only partially support qualitative accounts that non-native language use may influence bilingual parents' interaction behaviors with their young children. With growing rates of ASD diagnosis and increasing cultural/linguistic diversity around the world, further dedicated clinical and experimental attention to this issue is clearly warranted.